Not all sedentary behaviour is equal: Children's adiposity and sedentary behaviour volumes, patterns and types. Issue 6 (November 2018) - Shakir, Rima N.; Coates, Alison M.; Olds, Timothy; Rowlands, Alex; Tsiros, Margarita D.
Highlights: Rigorous, triangulated assessments of adiposity and sedentary behaviours were used. Sedentary behaviour volumes may be inconsistently linked with children's adiposity. Prolonged sedentary bouts and computer/game use may be related to adiposity in boys. Girls engaging in more non-screen sedentary behaviours may have lower adiposity. Abstract: Objective: The importance of different constructs of sedentary behaviours in relation to childhood obesity is uncertain. Thus, this study aimed to investigate relationships between volume, patterns and types of sedentary behaviour and adiposity in children. Methods: A case-control study was undertaken involving 234 children aged 10–13 years who were either of a healthy-weight (74 boys, 56 girls) or classified as obese (56 boys, 48 girls). Percent body fat (by dual-energy X-ray absorptiometry) and waist-to-height ratio were assessed. Time, type (television, videogame, computer, eating, passive transport) and bout length of sedentary behaviours were measured using accelerometry and the Multimedia Activity Recall for Children and Adolescents. Time use (total daily energy expenditure, sleep, physical activity), age, household income and Tanner stage were covariates in sex-stratified partial least squares analyses. Results: Daily energy expenditure and income were negatively associated with adiposity for both sexes. Television time was consistently positively associated with adiposity. In boys only, prolonged bouts of sedentary behaviour and time spent playing video games/computer were positively linked with adiposity. Non-screen sedentary behaviour was negatively associated with adiposity in girls. Independent of total energy expenditure, total sedentary time was only inconsistently associated with fatness. Conclusions: These data suggest that (1) characteristics of sedentary time other than duration are associated with adiposity in children, and (2) associations may be sex-specific.